RESEARCH ON SIGNAL COMPENSATION PROCESSES IN THERMAL INDUSTRIAL OBJECTS WITH DISTRIBUTED PARAMETERS - Mygushchenko, Ruslan; Kropachek, Olga; Finohenov, Oleksii; Poliakova, Tetiana (Bulletin of the National technical university "Kharkiv Polytechnic Institute" Series: Techniques in a machine industry, 2025)
The article examines a thermal industrial object with distributed temperature parameters. An information-geometric model based on transfer functions has been developed for the industrial object and a mathematical model has been determined. Additionally, a cross-coupling compensator has been synthesized. Sequential logarithmic identification method was used and studied to formulate the mathematical model of the object. Transmission coefficients, transport delay and time constants for each transfer function of the information-geometric model were calculated during this process. A compensator for three temperature channels was synthesized using matrix calculus approaches from linear algebra. Given the computational complexity of calculations, the authors developed and utilized specialized software capable of automatically real-time identification of smooth aperiodic transient responses and automatically synthesizing a cross-coupling compensator in real-time The Einstein digital temperature converter set was used for this purpose. It was assembled into a measurement channel with a digital output and a USB interface. The authors also investigated temperature stabilization channels in the studied industrial object using a PID controller and a relay actuator. A mathematical study of the amplitude and period of self-oscillations across the three control channels was conducted determining the impact of transport delay on the amplitude and period of temperature signal oscillations. Future research is planned for different types of industrial objects characterized by different transfer functions, specifically those involving high-frequency vibration processes. Vibration and its derivatives, namely vibrational displacement, velocity, and acceleration along with temperature, are among the most commonly monitored parameters in industrial applications.